Taqnin Al-Hakam in the Traffic of History - Yuni Amalia Rizal; Jailani Jailani (Prodi Magister Ilmu Agama Islam, Pascasarjana UIN Ar-Raniry, 2026)
Islamic law has undergone continuous development, in line with the advancement of contemporary legal knowledge. Initially, Islamic regulations were systematized through the ijtihad of jurists accumulated in fiqh books and through the decisions of court judges. Current legal developments, with the presence of systematic state regulations, require adjustments to the type of Islamic regulation organized through formal and binding state institutions. In the history of the Ottoman Caliphate, Sultan Sulaiman began to establish a law in the form of authority called qanun, so that Sultan Sulaiman of the Ottomans was known as Sulaiman al-Qanuni (1520-1560 CE). Where he diligently implemented the qanun or qanun name as an official regulation. The presence of qanun fiqh is seen as a necessity, while some view its presence as hindering the progress of ijtihad, which is one form of transformation towards Islamic law.